2017
DOI: 10.2174/1381612822666161006123530
|View full text |Cite
|
Sign up to set email alerts
|

The Insular Cortex and Takotsubo Cardiomyopathy

Abstract: Transient left ventricular dysfunction in patients under emotional stress, also known as Takotsubo cardiomyopathy, has been recognized as a distinct clinical entity. Recent studies have supported the concept notion that the cardiovascular system is regulated by cortical modulation. A network consisting of the insular cortex (Ic), anterior cingulate gyrus, and amygdala plays a crucial role in the regulation of the central autonomic nervous system in relation to emotional stress such as anxiety, fear and sadness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 3 publications
2
57
0
Order By: Relevance
“…In addition, recent studies have supported the notion that the cardiovascular system is regulated by a central autonomic network consisting of Ic, anterior cingulate gyrus and amygdala [3]. Oppenheimer et al [4] identified a site of cardiac representation within the Ic.…”
Section: Sirmentioning
confidence: 99%
“…In addition, recent studies have supported the notion that the cardiovascular system is regulated by a central autonomic network consisting of Ic, anterior cingulate gyrus and amygdala [3]. Oppenheimer et al [4] identified a site of cardiac representation within the Ic.…”
Section: Sirmentioning
confidence: 99%
“…In a dog model, the adjusted QT interval at high parasympathetic or low sympathetic tone was significantly longer than that at low parasympathetic or high sympathetic tone [2]. However, recent studies have supported the notion that the cardiovascular system is regulated by a cortical network consisting of the Ic, anterior cingulate gyrus and amygdala [3]. Several points should be taken into account when interpreting these results reported by Turri et al [1].…”
mentioning
confidence: 92%
“…In the early 1990s, reversible cardiomyopathy precipitated by acute emotional stress was reported . The patients were usually post‐menopausal women and often developed signs and symptoms of acute coronary syndrome proximate to a strong emotional stressor associated with a transient apical and mid‐ventricular wall motion abnormality despite the absence of obstructive coronary artery disease at the time of emergent coronary angiography . This syndrome was originally termed as Takotsubo cardiomyopathy .…”
mentioning
confidence: 99%
“…14,15 This syndrome was originally termed as Takotsubo cardiomyopathy. 15 Although the clinical manifestations of Takotsubo cardiomyopathy and those in HFrEF with DM are different, the status of post-menopausal women seems to be a common risk, and reduced oestradiol level might serve as a common underlying pathophysiology. The complexity for the relationship between sex steroid hormone and cardiovascular system gives us a glimpse to understand the precise pathophysiology in those disorders.…”
mentioning
confidence: 99%